A conceptual architecture of distributed web services for service ecosystems - Wu, Chen; Chang, Elizabeth (The International Society for Computers and Their Applications - ISCA, 2005)
The classical nature of centralized web services client/server architecture brings about many associated problems such as performance, bottlenecks, and scalability. Meanwhile some peer-to-peer research proposals have not respected the existing web services standards, thus leaving the compatibility and feasibility issue open. Hence existing web services architecture is not designed to accommodate large-scale, distributed, internet-wide applications. In this paper, we propose a conceptual architecture for distributed web services to enable web services-based software systems to "work well" in the heterogeneous and highly distributed service ecosystem environment.